2010
DOI: 10.1038/ki.2010.21
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Epstein–Fechtner syndromes owing to MYH9 R702 mutations develop progressive proteinuric renal disease

Abstract: Recent linkage analyses of nondiabetic African-American patients with focal segmental glomerulosclerosis (FSGS) have identified MYH9, encoding nonmuscle myosin heavy chain IIA (NMMHC-IIA), as a gene having a critical role in this disease. Abnormalities of the MYH9 locus also underlie rare autosomal dominant diseases such as May-Hegglin anomaly, and Sebastian, Epstein (EPS), and Fechtner (FTNS) syndromes that are characterized by macrothrombocytopenia and cytoplasmic inclusion bodies in granulocytes. Among thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
99
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(113 citation statements)
references
References 24 publications
12
99
0
2
Order By: Relevance
“…To demonstrate the utility of our method to detect glomerular dysfunction, we measured the simultaneous vascular clearance of dextrans after knockdown of zMyh9 and zApol1, respectively. Mutations in MYH9 and APOL1 are associated with chronic kidney disease in humans (3,8). However, it remains unclear whether zMyh9 and zApol1 serve similar or identical functions in zebrafish.…”
Section: ϫ19mentioning
confidence: 99%
“…To demonstrate the utility of our method to detect glomerular dysfunction, we measured the simultaneous vascular clearance of dextrans after knockdown of zMyh9 and zApol1, respectively. Mutations in MYH9 and APOL1 are associated with chronic kidney disease in humans (3,8). However, it remains unclear whether zMyh9 and zApol1 serve similar or identical functions in zebrafish.…”
Section: ϫ19mentioning
confidence: 99%
“…Previous work from human patients has suggested that the abnormalities found in the kidneys could reflect defects in the podocytes. 24 NMII-A partially colocalizes with the podocyte marker, synaptopodin in both A gfp /A ϩ and A gfpR702C /A ϩ glomeruli ( Figure 7C). Figure 7D provides evidence for altered podocyte architecture, typically foot process effacement, that is seen in the A D1424N /A D1424N mice.…”
Section: Kidney Abnormalities In the Point Mutant And Nmii-a Podocytementioning
confidence: 99%
“…Первые проявления нефропатии -протеинурия и микрогематурия, однако гематурия может быть и про-явлением тромбоцитопении [6,7,[17][18][19].…”
Section: рисунокunclassified